Reformation of Pawnbrokers Act 1972: A Comparative Study with Brunei - Adnan, Wan Nur Addibah; Mohamad, Nurul Fatin; Mohd Ruslan, Mohd Nazrin Hareez (Faculty of Law, 2012)
This research paper is a revision of pawn broking laws in Malaysia, by way of comparing it with the pawn broking system in Brunei. More specifically, the current laws being practised in Malaysia in regulating pawn broking transaction business are being revised and the provisions which have been found to be insufficient or prejudicial to the public will be compared to Brunei in order to solve the problem. To conduct this study, extensive research has been made pertaining to pawn broking practise in Malaysia and Brunei. The provisions in the current laws also have been referred to and an interview session with a few customers has been conducted to gain more information. The findings showed the list of the provisions which are in flaw and solution to the problems have been suggested by comparing it with pawn broking system in Brunei. Finally, some recommendations are made in order to ensure that better set of laws governing the pawn broking system in Malaysia can be guaranteed.